A corpus-based theory and lexicographic process for the inclusion of neologisms, archaisms and foreign loanwords in lexicons of Qeqchi Mayan - Frazier, Jeffrey Brent (Stellenbosch : Stellenbosch University, 2024)
Thesis (DPhil)--Stellenbosch University, 2024.